Pengaruh Birth Ball Terhadap Pengurangan Nyeri Dan Kecemasan Pada Kala I Persalinan Di PMB Pringsewu - kunang, Analia (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Baground: Chirldbirrth irs a natural procerss that erverry prergnant woman wirll erxperrirerncer. Most chirldbirrths arer accompanirerd by irnternser pairn, whirch can somertirmers causer trauma to ther motherr. Ther pairn durirng labor irs a common occurrerncer, wirth physirologircal and psychologircal factors contrirbutirng to irt. Oner non-pharmacologircal merthod to allervirater pairn and provirder comfort to ther motherr irn labor irs usirng a birrth ball. Objective: Ther airm of thirs study irs to derterrmirner ther erfferct of ther birrth ball merthod on rerducirng ther irnternsirty of labor pairn durirng ther actirver phaser of ther firrst stager of labor at BPM Prirngserwu. Method: Thirs rerserarch users a prer-erxperrirmerntal dersirgn wirth a oner-group prerterst-postterst dersirgn. Ther sampler sirzer irs 30 rerspondernts. Ther study populatiron irncluders all motherrs irn labor durirng ther firrst stager wirth cerrvircal dirlatiron of 6-8 cm, and ther samplirng terchnirquer userd irs purposirver samplirng. Data collerctiron terchnirquers irnvolver usirng a counterrprerssurer querstironnairrer wirth a birrth ball and ther VAS pairn scaler. Data analysirs irs perrformerd usirng pairrerd t-terst. Result: Ther rersults show that ther averrager pairn scaler of rerspondernts berforer treratmernt was 7.94, and afterr treratmernt, irt was 6.41. Statirstircal analysirs usirng pairrerd t-terst yirerlderd a sirgnirfircant rersult of 0.000, whirch irs smallerr than ther 5% sirgnirfircancer lerverl (P Valuer = 0.000 < 0.05). Conclution: Ther conclusiron irs that therrer irs an irnfluerncer of usirng ther birrth ball merthod on rerducirng labor pairn durirng ther actirver phaser of ther firrst stager of labor. Ther study suggersts that ther birrth ball merthod can ber userd as an alterrnatirver non-pharmacologircal therrapy irn ther managermernt of labor pairn durirng ther actirver phaser of ther firrst stager.